Langfærder og helleristninger - Kristiansen, Kristian (In Situ Archaeologica, 2002)
”Rock art ships and long distance sea travels in Scandinavia”: Long distance travels can be documented through the appearance of ”foreign” ships on local rock art panels. Traveling chiefs were in this way documenting their visits, sometimes along with other foreign motifs. This interpretation is based upon the observation that regional styles in ship carvings were common, and thus allows for a documentation of their appearance outside their territory. Furthermore, there is correspondence between person and carving in rock art, as it is immovable. The period 1700-1400 BC was a time of maritime adventures, documented in rock art, leading to the formation of a Nordic Bronze Age from 1500 BC, based upon highly developed and frequent interactions throughout Scandinavia, much of it sea based.